Internalization of Democracy Values Through “Majelis Permusyawaratan Kelas” Activities in Increasing Student Activity Participation in The School - Winandi, Aan; Yuliandari, Erna; Winarno, Winarno (Jurnal Civicus, 2024)
The aims of the research are to describe: 1) how to internalize democratic values through MPK activities. 2) The results of internalizing democratic values of MPK activities in increasing student participation. The study uses qualitative methods. Data collection techniques using interviews, observation, document analysis and questionnaires. Subject taking using purposive sampling technique. Location in MPK SMA Negeri 5 Surakarta. Testing validity of using source triangulation and method triangulation. Data analysis through data collection, data condensation, data presentation, and drawing conclusions. The results of the research show 1) the method of internalization that is applied is through activities organized by the organization, namely a) the student council supervisory work program; b) aspiration questionnaire work program; c) aspiration forum work program (Smaliska Speaks); d) extracurricular supervisory work program; e) work program for the election of OSIS and MPK chairpersons; f) open recruitment work program for new MPK members; g) work program accountability report. 2) The results of internalization are as follows: a) high attendance indicators; b) the indicator of the position held is a supporting factor, c) the indicator of being involved in organizational aspects is found in the awareness of students in participating; d) indicators of members' willingness to make sacrifices show they are willing to sacrifice their time, thoughts, energy, and materials; e) motivational indicators show that each student has different motivations. The results of the questionnaire show the level of participation of students in participating in MPK activities, which is in the medium category with a percentage of 36%.